What Factors Influence The Profitability Of Firms In Indonesia? Evidence From The Industrial Firms Listed On The Indonesia Stock Exchange - Lusiana Sartika; Diah Amalia (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The purpose of this study is to determine the effect of liquidity, interest coverage ratio, leverage, taxation aspects, non-debt tax shield, and asset tangibility on the profitability of industrial companies listed on the Indonesia Stock Exchange. This study employs a quantitative method, using the annual financial statements of industrial companies listed on the IDX as the object of study for the period from 2018 to 2022. The research sample employs a purposive sampling method, consisting of 185 participants. The study uses descriptive analysis and multiple linear regression. The results of the partial test study indicate that liquidity, leverage, and asset tangibility hurt profitability. The interest coverage ratio has a positive effect on profitability. Taxation aspects and Non-Debt Tax Shield do not effect profitability. The results of the simultaneous test indicate that liquidity, interest coverage ratio, leverage, taxation aspects, NDTS, and asset tangibility effect profitability.